Ir-6: A Novel Iridium (III) Organometallic Derivative for Inhibition of Human Platelet Activation - Ren-Shi Shyu; Themmila Khamrang; Joen-Rong Sheu; Chih-Wei Hsia; Marappan Velusamy; Chih-Hsuan Hsia; Duen-Suey Chou; Chao-Chien Chang (Bioinorganic Chemistry and Applications)
Platelet activation has been reported to play a major role in arterial thrombosis, cancer metastasis, and progression. Recently, we developed a novel Ir(III)-based compound, [Ir(Cp∗)1-(2-pyridyl)-3-(4-dimethylaminophenyl)imidazo[1,5-a]pyridine Cl]BF4 or Ir-6 and assessed its effectiveness as an antiplatelet drug. Ir-6 exhibited higher potency against human platelet aggregation stimulated by collagen. Ir-6 also inhibited ATP-release, intracellular Ca2+ mobilization, P-selectin expression, and the phosphorylation of phospholipase Cγ2 (PLCγ2), protein kinase C (PKC), v-Akt murine thymoma viral oncogene (Akt)/protein kinase B, and mitogen-activated protein kinases (MAPKs), in collagen-activated platelets. Neither the adenylate cyclase inhibitor SQ22536 nor the guanylate cyclase inhibitor 1H-[1,2,4]oxadiazolo[4,3-a]quinoxalin-1-one significantly reversed the Ir-6-mediated inhibition of collagen-induced platelet aggregation. Moreover, Ir-6 did not considerably diminish OH radical signals in collagen-activated platelets or Fenton reaction solution. At 2 mg/kg, Ir-6 markedly prolonged the bleeding time in experimental mice. In conclusion, Ir-6 plays a crucial role by inhibiting platelet activation through the inhibition of signaling pathways, such as the PLCγ2–PKC cascade and the subsequent suppression of Akt and MAPK activation, thereby ultimately inhibiting platelet aggregation. Therefore, Ir-6 is a potential therapeutic agent for preventing or treating thromboembolic disorders or disrupting the interplay between platelets and tumor cells, which contributes to tumor cell growth and progression.